Complete poems - Hemingway, Ernest, 1899-1961.; Gerogiannis, Nicholas; Hemingway, Ernest, 1899-1961. (Lincoln : University of Nebraska Press, 1992)
Collection of eighty eight poems by Hemingway.
"A Bison book.".
Rev. ed. of: 88 poems. 1979.
Includes bibliographical references (p. 167-170).
Young Adult
Keywords: American poetry; American poetry